Effects on the strength and durability of graphene oxide modified geopolymer concrete using industrial waste bauxite tailings - F.S. Frieda; S. Greeshma (Case Studies in Construction Materials)
Studies on sustainable practices in the construction industry have been on the rise as there are more concerns about the environmental effects of disposing of industrial solid waste. Bauxite tailings (BT), which is an industrial waste product in aluminium production, have a major disposal problem. Geopolymer concrete (GPC) is increasingly becoming a viable option to replace Ordinary Portland cement (OPC)-based concrete since it is less carbon-intensive and possesses improved mechanical and durability characteristics. The research in the field of nanotechnology has projected the future role of Graphene Oxide (GO) in extending the improvement of concrete properties. A literature review was conducted to identify the latest research on geopolymer concrete, industrial waste utilization, and modification using nanomaterials. Previous studies have indicated that GPC has desirable strength and durability properties, and with the addition of nanomaterials, it can be further improved in terms of its microstructure as well as its overall performance. Nevertheless, the impact of GO on BT-based GPC has yet to be extensively studied, which needs a systematic investigation to maximize its composition and evaluate its feasibility signifying a huge research gap that is targeted in this study. The present study evaluates the mechanical, durability, and microstructure properties of GO-modified GPC using BT and Ground Granulated Blast Furnace Slag (GGBS) as precursors under ambient curing. The experimental investigations were carried out with different dosages of GO (0.025 wt%, 0.005 wt%, 0.075 wt%, 0.01 wt% & 0.125 wt%) in GPC blends using sodium hydroxide of 4 M and sodium silicate in a ratio of 2.5 as alkaline activator solution. Compressive strength tests showed that the incorporation of 0.1 wt% GO offered considerable enhancements, where the GCM1-GO0.1 mixture (A/B = 0.4) had a 44.52 % improvement, followed by GCM2-GO0.1 (A/B = 0.45) and GCM3-GO0.1 (A/B = 0.5) with improvements of 31.95 % and 10.22 %, respectively. The durability properties were examined using the Rapid Chloride Penetration Test (RCPT), Water Permeability Test (WPT), Surface Resistivity (SR), and Ultrasonic Pulse Velocity (UPV). The addition of 0.1 wt% GO showed remarkable enhancements in durability, decreasing chloride permeability and water absorption but increasing surface resistivity and ultrasonic pulse velocity. In addition, correlation analysis among critical mechanical and durability parameters led to the generation of a prediction model for compressive strength, tensile strength, and surface resistivity. The resultant model was supported through comparisons against literature studies and appropriate design standards and codes to validate its performance and accuracy as a material prediction model. The Microstructural analysis using Scanning Electron Microscopy (SEM) and image processing confirmed enhanced geopolymerization and densification of matrix in GO-reinforced samples. The GO-modified BT-based GPC not only enhances mechanical strength and durability but also presents an environmentally friendly BT disposal method highlighting the prospect of using industrial waste materials to produce sustainable construction materials.